Role of novel protein acylation modifications in sepsis - Wang, Jing; He, Aifeng; Song, Lin; Jiang, Wei; Xu, Lu; Zheng, Ruiqiang; Yu, Jiangquan (Frontiers in Immunology, 2025)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection, exhibiting high global morbidity and mortality. Accumulating evidence indicates that post-translational modifications (PTMs), as pivotal epigenetic mechanisms, play a crucial role in regulating diverse biological processes. The significance of PTMs in sepsis is increasingly recognized, as they may influence disease progression by modulating protein stability, activity, and localization. In recent years, advances in mass spectrometry have elucidated a series of novel PTMs, including succinylation (Ksucc), S-palmitoylation, lactylation (Kla), crotonylation (Kcr), 2-hydroxyisobutyrylation (Khib), β-hydroxybutyrylation (Kbhb), and malonylation (Kmal). This review presents the first comprehensive analysis of the characteristics, functions, and implications of these seven lysine acylation modifications in the pathogenesis and progression of sepsis, aiming to provide valuable insights for diagnosis and therapeutic intervention.